Planificación Turística y Desarrollo Sostenible de la parroquia Punín, cantón Riobamba, provincia de Chimborazo. - Morocho Guaraca, Edwin Maximo (2023)
Through the research project Tourism Planning and Sustainable Development of the Punín Parish, where the great potential it has to strengthen the use of natural and cultural resources is evidenced in such a way that the main problem detected is inadequate sustainable development. The general objective is to analyze the incidence with tourism planning to work on the problem. The research methods are descriptive, documentary, non-experimental and transversal, with which information was collected, such as the description of characteristics, phenomena, and individuals to study the problem of our independent and dependent variables to achieve the results that we use as a technique for collecting information, the survey and the questionnaire as an instrument. In addition, a random probabilistic test was carried out for the independent and dependent variables to collect information through the application of instruments. Likewise, with the SPSS version 25 hypothesis test, it was verified that tourism planning has no influence on sustainable development. Finally, for the development of the proposal, the conclusions and recommendations obtained in the application of surveys with the different statistical calculations made were taken as a reference, for which the following was proposed: Tourism strategies that contribute to sustainable development in the Punín Parish, Riobamba canton, to achieve a better quality of life for the inhabitants that allows the opening of new projects and encourages the authorities of (GADPR Punín), to be part of the benefits that an adequate, sustainable development can have.